Characterization of the Effect of a Novel γ-secretase Modulator on Aβ: A Clinically Translatable Model - Portelius, Erik; Appelkvist, Paulina; Stromberg, Kia; Hoglund, Kina (Current Pharmaceutical Design, 2014)
Alzheimer's disease (AD) is a slowly progressing disease and the evaluation of clinical effects of candidate drugs requires large clinical cohorts as well as long treatment trials. There is a great need for central biomarkers and translatable pre-clinical models to provide early indication of treatment effects. We set out to evaluate the guinea pig as a clinically translatable model looking at Aβ peptides. Our data demonstrate homology between β-amyloid (Aβ) peptide pattern in cerebrospinal fluid (CSF) from human and guinea pig. To further evaluate the model a novel γ-secretase modulator was used. Dose and time response studies confirm the modulatory properties with a statistically significant decrease in relative levels of Aβ1-40, Aβ1-42 and increase in Aβ1-37 already one hour after administration. We suggest that the guinea pig is a compelling pre-clinical model for evaluating and translating central effects on Aβ peptides in CSF after treatment. Further quantitative data are needed to confirm our data together with data from clinical trials in order to back translate and validate our findings.
Keywords: Alzheimer' s disease